Synthesis and anticonvulsant activity of 6-methyl-2-((2-oxo-2-arylethyl)thio)pyrimidin-4(3 H)-one derivatives and products of their cyclization - Hanna I. Severina; Olga O. Skupa; Natalya I. Voloshchuk; Marharyta M. Suleiman; Victoriya A. Georgiyants (Pensoft Publishers, 2019)
The alkylation of 6-methyl-2-thioxo-2,3-dihydro-1H-pyrimidine-4-one phenacyl bromides under different conditions was investigated. It was found that during the reaction in the medium of DMF/K2CO3 a mixture of 2-(2-aryl-2-oxoethyl)thio-6-methyl-pyrimidine-4(3H)-one and 3-hydroxy-3-aryl-7-methyl-2,3-dihydro-5H-thiazolo[3,2-a]pyrimidine-5-one was formed. The holding of the resulting mixture in the concentrated sulphuric acid leads to the formation of cyclization products - derivatives of 3-aryl-7-methyl-5H-thiazolo[3,2-a]pyrimidin-5-one with high yields. Individual S-alkylated derivatives - 2-(2-aryl-2-oxoethyl)thio-6-methyl-pyrimidine-4(3H)-one - were obtained by reacting in methanol in the presence of sodium methoxide. Pharmacological screening of synthesized compounds for anticonvulsant activity on the model of pentylenetetrazole seizures in rats was carried out and some regularity "structure-activity" was established.